"El conflicto cultural" "El choque de las civilizaciones y la reconfiguración del orden mundial", de Samuel Huntington. Ed. Paidós, Madrid, 1997. - Domínguez, Cristina (1997)
Fil: Domínguez, Cristina. Pontificia Universidad Católica Argentina; Argentina